Biodiversidad de los hongos fitopatógenos del suelo de México - González, Ma. Del Pilar (Instituto de Ecología, A.C., 2001)
In México soilborne plant fungi studies have been mainly focused on their biology, damage, control (mainly biológica! control) and economic losses produced on economical important crops. Most of research has been done on genera Phytophthora, Fusarium, Rhizoctonia, Pythium y Phymatotrichum due to their wide host range, worlwide distribution and high crop damages. However, there is a need for more comprehensiva studies of the diseases dynamic behavior caused by these soilborne plant fungi and the components involved in the disease expression: the pathogen, the host and the environment. Future research in México should focus towards a biological and ecological integration of studies in order to build a rational and sustainable management of plant diseases in agroecosystems. It will be aiso required to have studies with more consisteney and spatio-temporal continuity in order to get historical data records of the diseases caused by soilborne plant fungi in the major importance crops in the country. This will allow forecasting and avoidance of future severe epidemic damage. Sustainable soil management aiso requires regulation and normativíty of soil use in mexican agroecosystems.